Clinical significance of Kelch-like protein 11 antibodies. Issue 3 (May 2020) - Maudes, Estibaliz; Landa, Jon; Muñoz-Lopetegi, Amaia; Armangue, Thaís; Alba, Mercedes; Saiz, Albert; Graus, Francesc; Dalmau, Josep; Sabater, Lidia
Abstract : Objective: To report the clinical and oncologic associations of antibodies against Kelch-like protein 11 (KLHL11-ab), recently suggested as biomarkers of a paraneoplastic brainstem cerebellar syndrome associated with testicular seminoma, and to determine the value of immunohistochemistry as a screening technique. Methods: Studies included 432 sera or CSF from 329 patients with paraneoplastic (157) or autoimmune neurologic syndromes (172); 63 with neurologic symptoms and benign teratomas; 28 with small-cell lung cancer, and 12 healthy subjects. KLHL11-abs were examined using a cell-based assay (CBA) with HEK293 cells transfected with a human KLHL11 clone. The CBA specificity was confirmed by immunoprecipitation. All positive samples were examined by immunohistochemistry on rat brain sections. Results: KLHL11-abs were detected in 32 patients by CBA, and patients' antibodies immunoprecipitated KLHL11. Using rat brain immunohistochemistry, only 7 samples (22%) were positive. Patients' median age was 28 years (range 9–76 years), and 16 (50%) were women. Tumors were identified in 23/32 (72%) patients, including 14 teratomas and 7 seminomas or mixed germ cell tumors. Thirteen (41%) patients had cerebellar ataxia (7) or encephalitis with brainstem cerebellar symptoms (6), 7 (22%) anti-NMDA receptor (NMDAR) encephalitis (5 with ovarian teratoma), 5 (16%) opsoclonus-myoclonus, 3 (9%) limbic encephalitis, and 4 (12%) diverse neurologic symptoms (3 with benign teratomas). Concurrent autoantibodies occurred in 14 (44%) patients (7 anti-NMDAR, 6 Ma2, and 1 Hu). Conclusions: KLHL11-abs associate with a spectrum of syndromes and tumors wider than those previously reported; 44% of patients have concurrent neuronal antibodies, some of them (anti-NMDAR) pathogenically relevant. Brain immunostaining is not useful for routine screening of KLHL11-abs.